Influence of Socio-Economic Status on Psychopathology in Ecuadorian Children - Pérez-Marfil, María Nieves; Fernández-Alcántara, Manuel; Fasfous, Ahmed F.; Burneo-Garcés, Carlos; Pérez-García, Miguel; Cruz-Quintana, Francisco (Frontiers in Psychiatry, 2020)
The socioeconomic status (SES) of parents has been reported to have a crucial impact on emotional competence in childhood. However, studies have largely been carried out in developed countries and in children in a specific age range, and it is not clear whether the effect of the SES of parents varies by age. The objective of this study was to investigate the psychopathological profile (including externalizing and internalizing problems) of children aged 7, 9, and 11 years old with low SES in a developing country (Ecuador). The study included 274 children (139 boys and 135 girls), who were divided between Medium-SES (n=133) and Low-SES (n=141) groups. Data were gathered on socioeconomic and anthropometric variables of the children, and the parents completed the Child Behavior Check-List (CBCL). In comparison to the Medium-SES group, children in the Low-SES group obtained higher scores for internalizing and externalizing symptoms and for total problems, and they obtained lower scores for social competence skills. The housing risk index and school competence were the two main predictors of internalizing and externalizing problems in this population.